Nanomaterials for miRNA detection: the hybridization chain reaction strategy. Issue 1 (21st December 2022) - Mohan, Brij; Kumar, Sandeep; Kumar, Suresh; Modi, Krunal; Tyagi, Deependra; Papukashvili, Dimitri; Rcheulishvili, Nino; Pombeiro, Armando J. L.
Abstract : MicroRNAs (miRNAs) with nucleotides are a class of endogenous small RNAs and can play crucial functions in diagnosing diseases. Abstract : MicroRNAs (miRNAs) with nucleotides are a class of endogenous small RNAs and can play crucial functions in diagnosing diseases. In particular, the group of miRNAs is responsible for information related to the cell and disease. Among various techniques for miRNA detection, the hybridization chain reaction (HCR) strategy shows potential and efficiency. This review summarizes and studies the most efficient HCR strategy for detecting miRNA using nanomaterials due to their ultrasensitive detection and excellent performances. In addition, signal amplification for the sensitive detection of miRNA due to the chain reaction has been studied. The key factors, such as limit of detection (LOD), linear range, the importance of the strategy, limitations or challenges, and future perspective are described. Finally, the study will provide new findings for developing a miRNA detection strategy applicable to disease diagnosis.